Mindfulness-based group intervention in adolescents at-risk for excess weight gain: A randomized controlled pilot study. (1st September 2019) - Shomaker, Lauren B.; Berman, Zoe; Burke, Morgan; Annameier, Shelly K.; Pivarunas, Bernadette; Sanchez, Natalia; Smith, Amy D.; Hendrich, Silas; Riggs, Nathaniel R.; Legget, Kristina T.; Cornier, Marc-Andre; Melby, Christopher; et al.
Abstract: Objectives: To assess feasibility/acceptability of a mindfulness-based approach to excess weight prevention in adolescents at-risk for excess weight gain. To pilot test efficacy of a mindfulness-based intervention for improving food reward sensitivity, stress-eating, executive function (EF), and BMI/adiposity. Methods: A pilot randomized controlled trial was conducted with 12–17y adolescents at-risk for excess weight gain based on above-average weight (body mass index [BMI]≥70%ile) or parental history of obesity (BMI≥30 kg/m 2 ). Adolescents were randomized to a mindfulness-based ( n = 29) or health education control group ( n = 25) that met for six weekly one-hour sessions. Feasibility/acceptability were determined from attendance and acceptability survey ratings. At baseline, six-week and six-month follow-up, adolescents' perceived stress was measured with the Perceived Stress Scale, food reward sensitivity with a behavioral task, stress-eating during a laboratory test meal, and EF with the parent-reported Behavior Rating Inventory of Executive Function and NIH Toolbox. At the same intervals, BMI indices and body fat by air displacement plethysmography were assessed in a fasted state. Results: Median session attendance was 6:6 sessions in both conditions; program acceptability ratings were above-average. Compared to health education, adolescents in mindfulness had lower food reward sensitivity at six-months (Cohen's d = 0.64, p = .01). There were no between-condition differences in BMI (mindfulness vs. health educationΔsix-months 95%CI 0.20, 1.52 kg/m 2 vs. 0.21, 1.62 kg/m 2 ) or adiposity (−3.64, −0.61% vs. −4.31, −1.04%) changes. Conclusions: A mindfulness-based group intervention is feasible/acceptable among adolescents at-risk for excess weight. In this pilot sample, mindfulness and health education were equivocal for BMI/adiposity outcomes. Future trials with a larger, adequately-powered sample and longer-term follow-up are necessary to test efficacy of a mindfulness-based intervention for food reward sensitivity, stress-eating, EF, and stabilizing growth trajectories in youth at-risk for adult obesity.